Alpha-fetoprotein level in fetuses, infants, and children with ovarian masses: a literature review - Matonóg, Aleksandra; Drosdzol-Cop, Agnieszka (Frontiers in Endocrinology, 2024)
Alpha-fetoprotein is a serum protein highly produced during the fetal period, which is also known as a biomarker of various pathologies. Commonly, tumors requiring diagnosis and monitoring by AFP determination appear during the first year of age, with a poorer outcome when presenting in fetal life. Due to the advancement of examination technology, the detectability of ovarian masses in infants is higher. However, using the AFP as a biomarker could improve diagnosis in cases when imaging and histological examinations are not sensitive enough to detect the tumor. From the outcome of our investigation, it is possible to conclude that there is evidence to between increased α-fetoprotein level and ovarian masses. However, previous studies present contradictory and unverified results and their authors emphasized that future research are needed. In this article analysis of available literature about alpha-fetoprotein as a biomarker of ovarian masses in children was done. Two types of literature were reviewed: guidance and published studies (clinical trials, reviews, and systematic reviews). We queried EMBASE, PubMed and ScienceDirect and Web of Science databases to collect essential data.